DESIGNING ICT COMPETENCES – INTEGRATED SYLLABUSES OF SPEAKING COURSES (DESIGN AND DEVELOPMENT STUDY OF ENGLISH LANGUAGE EDUCATION PROGRAM SYLLABUSES) - Fadhilah Hamid, Syifa; Sulistyaningrum, Siti Drivoka (IJLECR (International Journal of Language Education and Cultural Review), 2019)
ICT implementation has been broadly used in all sectors of human‘s life including education. One of the ICT implementations in education is integrating ICT into curriculum, syllabus or course outline. Meanwhile, speaking has become a skill that utmost significance to acquire. Thus, this study aims at designing ICT competences integrated – speaking syllabuses for English Language Education Study Program (ELESP) by analyzing the existing speaking syllabuses from various universities in Indonesia. The analysis involved the ICT competences proposed by UNESCO, Digital Media Descriptors of English Profiling Grid (EPG) and other ICT based – theories. The study applied Design and Development Research (DDR) as the research design and qualitative as the research method. The stages of DDR in this study are Need Analysis; Describe the Objectives, Design and Develop the Syllabus, Evaluate the Prototypical Syllabus, Design Revision. The result of the study revealed that the ICT competences are mostly integrated in the component of Teaching Method or Classroom Activities and Learning Media in the syllabuses. The most applied level of ICT competences in the existing syllabuses is Knowledge Deepening level. However, the integration or infusions of ICT competences were explicitly or implicitly mentioned in the syllabuses of speaking subject. The study provides procedure of ICT integration and the design of ICT competences integrated – speaking syllabuses; General Speaking, Professional Speaking and Academic Speaking. The proposed syllabuses implemented the skill based syllabus and functional – notional syllabus design.